2003
DOI: 10.1038/sj.onc.1206133
|View full text |Cite
|
Sign up to set email alerts
|

Interferon regulatory factor-1 (IRF-1) is a mediator for interferon-γ induced attenuation of telomerase activity and human telomerase reverse transcriptase (hTERT) expression

Abstract: Constitutive activation of the telomerase is a key step in the development of human cancers. Interferon-c (IFN-c) signaling induces growth arrest in many tumors through multiple regulatory mechanisms. In this study, we show that IFN-c signaling represses telomerase activity and human telomerase reverse transcriptase (hTERT) transcription, and suggest that this signaling is mediated by IRF-1. Ectopic expression of IRF-1 attenuated hTERT promoter activity. Murine embryonic fibroblasts (MEFs) genetically deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 56 publications
2
34
0
Order By: Relevance
“…While this could be explained by an inability of the human promoter to drive transgene expression in mouse tissues, recent publications have shown that the hTERT promoter was highly active in mouse tumor cell lines but not in normal murine cells. 48,49 Similarly, we observed that AdhTERTp-E1A virus transduction of telomerase-expressing murine cancer cell lines B10.2 and C57 at MOI of 100 or higher resulted in significant killing of both cell types (Wang and Majumdar, unpublished observation). Normal histopathology was observed in liver and spleen samples of mice after systemic administration of AdhTERTp-E1A virus in contrast to the pronounced morphological abnormalities detected in the liver and spleen samples of mice treated with AdCMVp-E1A construct (Fig 6 and data not shown).…”
Section: Discussionmentioning
confidence: 79%
“…While this could be explained by an inability of the human promoter to drive transgene expression in mouse tissues, recent publications have shown that the hTERT promoter was highly active in mouse tumor cell lines but not in normal murine cells. 48,49 Similarly, we observed that AdhTERTp-E1A virus transduction of telomerase-expressing murine cancer cell lines B10.2 and C57 at MOI of 100 or higher resulted in significant killing of both cell types (Wang and Majumdar, unpublished observation). Normal histopathology was observed in liver and spleen samples of mice after systemic administration of AdhTERTp-E1A virus in contrast to the pronounced morphological abnormalities detected in the liver and spleen samples of mice treated with AdCMVp-E1A construct (Fig 6 and data not shown).…”
Section: Discussionmentioning
confidence: 79%
“…In previous reports, we demonstrated that IFN-c down-regulates hTERT expression, which is mediated by IRF-1 [7]. Exploring further down stream of IFN-c/IRF-1 signaling, p27 was uncovered as a possible inhibitory mediator of hTERT expression.…”
Section: Ifn-c Increases P27 Protein Level Through Irf-1mentioning
confidence: 99%
“…Previously, a novel anti-cancer mechanism of interferon c (IFN-c)/interferon regulatory factor-1 (IRF-1) signaling that down-regulates hTERT expression was suggested [7]. In an attempt to identify the potential regulator(s) of the IFN-c/IRF-1 signaling involved in suppressing hTERT expression and telomerase activity, we found that p27, a member of a cyclin-dependent kinase inhibitor (CDKI) family, has potent inhibitory effects on hTERT expression in human cervical cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…IFN-g efficacy in the clinical treatment of various cancers has also been reported, which has prompted the development and testing of IFN-g-based cancer gene therapy. [4][5][6] Delivery of the therapeutic genes to target sites in gene therapy has been explored using several approaches. One approach, which utilizes an intravascular injection of naked plasmid DNA encoding cytokine gene, has attracted attention lately as a novel method of controlling the in vivo pharmacokinetics of naked plasmid DNA.…”
Section: Introductionmentioning
confidence: 99%